Ultra relativistic electron beam spatial size estimation from angular distribution of their radiation in thin crystals - Goponov, Yu.A.; Sidnin, M.A.; Sumitani, K.; Takabayashi, Y.; Vnukov, I.E. (Вопросы атомной науки и техники, 2015)
The use of ultra relativistic electron (positron) emission in thin crystals to estimate particle beam spatial sizes for projected electron-positron colliders is proposed. The existing position-sensitive X-ray range detectors and the average path of secondary electrons in a detector restrict the minimum value of the measured beam size to a level of approximately 10 μm, which is far greater than the planned sizes of collider beams. We propose to estimate the electron (positron) beam divergence over the diffracted transition radiation from angular distribution measurements. The spatial size can be obtained from the calculated beam emittance or the experimental emittance, which is measured during the earlier stage of acceleration using optical methods. The problem of crystal destruction under the influence of a high intensity electron beam is discussed. The use of surface parametric X-ray radiation, where the problem of crystal destruction is almost absent, to measure the electron beam parameters is discussed.